2012
DOI: 10.4103/0972-0707.101891
|View full text |Cite
|
Sign up to set email alerts
|

Flexural strength of a composite resin light cured with different exposure modes and immersed in ethanol or distilled water media

Abstract: Aim:The aim of this in vitro study was to evaluate the flexural strength of a composite resin polymerized with three different modes of light exposure.Materials and Methods:The three different modes of light exposure were conventional, 600 mW/cm2/40s; soft start, 300 mW/cm2/10s + 600 mW/cm2/30s; pulse delay, 600 mW/cm2/1s + 60 s of waiting time + 600 mW/cm2/39s). Twenty samples were prepared for each polymerization method. Flexural strength (FS) tests were carried out with a 2 kN load at a speed of 0.5 mm/ min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…These results corroborate with other studies that have also demonstrated a direct relation between radiant exposure and flexural properties of composite resins. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate with other studies that have also demonstrated a direct relation between radiant exposure and flexural properties of composite resins. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…While flexural strength signifies the highest stress experienced by the composites before they fail, flexural modulus represents their stiffness. Flexural testing results in complex tensions stemming from the integration of compression, shear and tensile stresses (dos Santos et al, 2012). Different clinical situations necessitates the use of composites with dissimilar flexural strength and modulus (Anusavice, 2003, Rodrigues et al, 2007, Yap et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…ISO 4049 flexural test specimens are typically 25 mm long (International Organization for Standardization, 2000). These elongated composite specimens are technically challenging to fabricate and require the use of several overlapping light irradiation owing to the relatively smaller light exit windows of most curing tips (dos Santos et al, 2012). As the mesio-distal widths of molars are usually around 11 mm, the ISO recommended length is also not really clinically appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Diametral tensile testing is a common method for measuring the tensile strength of brittle materials because it avoids some of the difficulties inherent in direct and flexural tensile testing. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%